Motoneuronal Spinal Circuits in Degenerative Motoneuron Disease - Falgairolle, Mélanie; O’Donovan, Michael J. (Frontiers in Molecular Neuroscience, 2020)
The most evident phenotype of degenerative motoneuron disease is the loss of motor function which accompanies motoneuron loss. In both amyotrophic lateral sclerosis and spinal muscular atrophy, it is now clear that dysfunction is not restricted to motoneurons but is manifest in the spinal circuits in which motoneurons are embedded. As mounting evidence shows that motoneurons possess more elaborate and extensive connections within the spinal cord than previously realized, it is necessary to consider the role of this circuitry and its dysfunction in the disease process. In this review, we ask if the selective vulnerability of the different motoneuron types and the relative disease-resistance of distinct motoneuron groups can be understood in terms of their intraspinal connections.